Optimal social security claiming behavior under lump sum incentives: Theory and evidence - Raimond Maurer; Olivia S. Mitchell; Ralph Rogalla; Tatjana Schimetschek (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
Many Americans claim Social Security benefits early, though this leaves them with lower benefits throughout retirement. We build a lifecycle model that closely tracks claiming patterns under current rules, and we use it to predict claiming delays if, by delaying benefits, people received a lump sum instead of an annuity. We predict that current early claimers would defer claiming by a year given actuarially fair lump sums, and the predictions conform with respondents' answers to a strategic survey about the lump sum. In other words, such a reform could provide an avenue for encouraging delayed retirement without benefit cuts or tax increases. Moreover, many people would still defer claiming even for smaller lump sums.
urn:nbn:de:hebis:30:3-515311
Keywords: G11; G22; H55; J26; J32; 330; retirement; annuity; delayed claiming; pension; early retirement; Social Security